Free Vibration of the Axially Loaded System of Two Beams Connected by Two-Directional Viscoelastic Interlayer - Cabanska-Placzkiewicz, K. (Проблемы прочности, 2000)
In this paper the analytical method has been
used for solving a problem of free vibration
with clamping of the axially loaded sandwich
beam. The sandwich beam consists of two
external layers connected by viscoelastic
two-directional Winkler’s interlayer. The upper
external layer is described as the
Bernoulli-Euler’s model, which is loaded by
the constant axial force. The lower external
layer is modeling as the Timoshenko’s model.
The phenomenon of free vibration has been
described using a homogenous system of
conjugate partial differential equations. After
separation of variables in the system of
differential equations the boundary problem has
been solved and three complex equations for
definition of frequency and modes of free
vibration have been obtained. The free
vibration problem for arbitrarily assumed initial
conditions and various axial forces has been
considered. Предлагается аналитический метод решения задач о свободных колебаниях с затуханием
слоистых балок, состоящих из двух внешних слоев, соединенных внутренним вязкоупругим
слоем, который рассматривается как двунаправленное винклеровское основание. Верхний
внешний слой, нагруженный осевой постоянной силой, описывается на основе модели
Бернулли-Эйлера. Нижний внешний слой моделируется с помощью модели Тимошенко. Свободные
колебания описываются однородной системой связанных дифференциальных уравнений
в частных производных. После разделения переменных в исходной системе дифференциальных
уравнений решается краевая задача. В результате получено три комплексных
уравнения для определения частот и мод свободных колебаний. Задача о свободных
колебаниях рассмотрена для произвольных начальных условий и различных осевых сил. Запропоновано аналітичний метод розв’язку задач про вільні коливання зі
згасанням шаруватих балок, що складаються з двох зовнішніх шарів, з ’єднаних
внутрішнім в ’язкопружним шаром. Останній розглядається в якості
двонапрямленої вінклерівської основи. Верхній зовнішній шар, що навантажується
осьовою постійною силою, описується на основі моделі Бернул-
лі-Ейлера. Нижній зовнішній шар моделюється за моделлю Тимошенка.
Вільні коливання описуються однорідною системою зв’язаних диференціальних
рівнянь в частинних похідних. Після розділення змінних у вихідній
системі диференціальних рівнянь розв’язується крайова задача. У результаті
отримано три комплексних рівняння для визначення частот і мод вільних
коливань. Задача про вільні коливання розглянута для довільних початкових
умов і різних осьових сил.